2007
DOI: 10.1130/g23665a.1
|View full text |Cite
|
Sign up to set email alerts
|

Ages for the Big Stone Moraine and the oldest beaches of glacial Lake Agassiz: Implications for deglaciation chronology

Abstract: Glacial Lake Agassiz has been implicated as the trigger for numerous episodes of abrupt climate change at the close of the last ice age, yet the beginning age of the lake has never been determined. Here we report the fi rst numerical age data on the Big Stone Moraine and the oldest beaches of glacial Lake Agassiz. Organic remains from lakes, bogs, and channels distal to, and inset to, the Big Stone Moraine require that glacial activity at this moraine ceased prior to 12,000 14 C yr B.P. (13,950 cal [calendar] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…The Cass phase is not relevant here because Lake Agassiz existed only south of the Canada-United States border. Most researchers have concluded that the H-N-T beaches were formed during the Lockhart Phase (e.g., Fenton et al, 1983;Fisher, 2005;Lepper et al, 2007).…”
Section: General History Of the Early Stages Of Lake Agassizmentioning
confidence: 97%
See 1 more Smart Citation
“…The Cass phase is not relevant here because Lake Agassiz existed only south of the Canada-United States border. Most researchers have concluded that the H-N-T beaches were formed during the Lockhart Phase (e.g., Fenton et al, 1983;Fisher, 2005;Lepper et al, 2007).…”
Section: General History Of the Early Stages Of Lake Agassizmentioning
confidence: 97%
“…The Lockhart Phase began when ice retreated from the Red River Valley, which occurred earlier in the southern region, 12.2-11.0 14 C kyr BP (~14.2-12.9 cal kyr BP) (see Clayton and Moran, 1982;Fenton et al 1983;Dyke, 2004;Lepper et al, 2007), and ended with the beginning of the Moorhead phase, when the level of Lake Agassiz dropped by tens of metres, due to the opening of a lower outlet before 10.7 14 C kyr BP (12.7 cal kyr BP) (Leverington et al, 2000;Fisher et al, 2008). There are no radiocarbon dates from sediments of the H-N-T series of beaches, so until recently assignment of ages mainly has been based on relationships to dated events in Lake Agassiz overflow channels, to dated ice-margin positions, and to sediments of the Moorhead low-water phase of the lake.…”
Section: General History Of the Early Stages Of Lake Agassizmentioning
confidence: 98%
“…Possessing a total length of 534 km (355 mi) and a gradient of 24 cm/1.6 km (9.5 in/mi), the Minnesota River comprises a classic underfit stream. Formed by glacial River Warren, which breached a recessional moraine of the Des Moines Lobe bordering the southern end of glacial Lake Agassiz (a massive early Holocene freshwater lake encompassing over 100,000 mi 2 ) the Minnesota River Valley at Mankato measures about 2,470 m (9,000 ft) across and over 70 m (200 ft) deep (Ojakangas & Matsch 1982;Lepper et al 2007). Downstream, its annual discharge into the Mississippi averages 141 m 3 /sec (5,000 cfs), although it can range as high as 2,820 m 3 /sec or 100,000 cfs (Waters 1987).…”
Section: Study Site and Objectivesmentioning
confidence: 99%
“…In recent years, optical dating has been applied in a number of settings in the upper Midwest in an attempt to better constrain the chronology of late glacial events by directly dating proglacial sediment (Hooyer, 2007;Lepper et al, 2007;Fisher et al, 2008;Rawling et al, 2008;Schaetzl and Forman, 2008). As important as these contributions have been to our understanding of the late Pleistocene in these areas, constraining the timing of ice-marginal positions has remained an elusive goal in the upper Midwest.…”
Section: Introductionmentioning
confidence: 98%